Analysis of high school students' critical thinking ability in Bantul Regency on endocrine system material - Eka Mustika Sari; Evy Yulianti (University of Muhammadiyah Malang, 2024)
Critical thinking is an essential ability for students in the 21st century, particularly in complex subjects like the endocrine system in biology, which requires a deeper conceptual understanding. This study aims to analyze the critical thinking ability profile of Grade XI high school students in Bantul Regency on the topic of the endocrine system, a subject often considered difficult due to its abstract nature. This research is a descriptive quantitative study using a purposive sampling technique, involving 260 Grade XI students from various high schools in Bantul Regency. The test used consists of 8 essay questions, designed based on Ennis’ critical thinking aspects. The results reveal that the overall critical thinking ability of these students is still very low. Specifically, the percentage results for each aspect are as follows: the elementary clarification aspect is 37.8% with a very low category, the basic support aspect is 47.4% with a low category, the inference aspect is 25.5% with a very low category, the advance clarification aspect is 54.2% with a low category, and the strategy and tactics aspect is 47.8% with a very low category. These results provide a broader understanding of the critical thinking ability of Grade XI high school students in Bantul Regency, which can serve as a basis for educators in developing and designing various learning innovations aimed at enhancing pupils' capacity for critical thought.